Cancer incidence and prevalence in cystic fibrosis patients with and without a lung transplant in France - Rousset-Jablonski, Christine; Dalon, Faustine; Reynaud, Quitterie; Lemonnier, Lydie; Dehillotte, Clémence; Jacoud, Flore; Berard, Marjorie; Viprey, Marie; Van Ganse, Eric; Durieu, Isabelle; Belhassen, Manon (Frontiers in Public Health, 2022)
Background: Cystic fibrosis (CF) care and the life expectancy of affected patients have substantially improved in recent decades, leading to an increased number of patients being diagnosed with comorbidities, including cancers. Our objective was to characterize the epidemiology of cancers between 2006 and 2017 in CF patients with and without a lung transplant. Methods: Medical records of CF patients from 2006 to 2016 in the French CF Registry were linked to their corresponding claims data (SNDS). The annual prevalence and incidence rates of cancers were estimated from 2006 to 2017 in CF patients without lung transplant and in those with lung transplant after transplantation. Results: Of the 7,671 patients included in the French CF Registry, 6,187 patients (80.7%) were linked to the SNDS; among them, 1,006 (16.3%) received a lung transplant. The prevalence of any cancer increased between 2006 and 2017, from 0.3% to 1.0% and from 1.3% to 6.3% in non-transplanted and transplanted patients, respectively. When compared to the general population, the incidence of cancer was significantly higher in both non-transplanted (Standardized Incidence Ratio (SIR)= 2.57, 95%CI 2.05 to 3.17) and transplanted (SIR= 19.76, 95%CI 16.45 to 23.55) patients. The median time between transplant and the first cancer was 3.9 years. Among the 211 incident cancer cases, the most frequent malignant neoplasms were skin neoplasm (48 cases), lung cancers (31 cases), gastro-intestinal (24 cases) and haematologic cancers (17 cases). Conclusion: The overall burden of cancer in CF patients is high, particularly following lung transplantation. Therefore, specific follow-up, screening and cancer prevention for CF patients with transplants are necessary.